Evaluación del rendimiento de una bomba de calor asistida por energía solar que funciona con un compresor de 1/6 hp mediante el uso de refrigerantes R12 - R407C - R410A como fluidos de trabajo. - Rodríguez Guzmán, Iván Alejandro (2018)
The present research develops the performance analysis of a solar energy assisted heat pump with direct expansion evaluating refrigerants R12, R410A, R407C and R290 as possible working fluids, the components of this pump are: a 1/6 hp compressor, an electronic expansion valve, a copper condenser, and a collecting plate which in turn functions as a black-painted evaporator to increase the emissivity of that plate. Due to the environmental situation of the planet has investigated the characteristics of the refrigerants mentioned and proposes the use of the refrigerant more environmentally friendly, this refrigerant is the R290, refrigerant which have obtained their thermodynamic properties through the database provided by the software EES. The tests carried out have been tabulated with experimental data taken every five minutes in four different days carrying out five tests per day evaluating different climatic situations. The maximum water temperature, which was reached in the tests is 45 °C, the time that the equipment takes to heat the water depends on the climatic condition that it has, for example on sunny days with an average radiation of 422.35 W⸱m-2 and an ambient temperature of 14.26 °C the equipment took 40 minutes to reach the water temperature of 45 °C. The efficiency of the solar assisted system was in an optimum range obtaining values for the operating coefficient (COP) between 3.58 and 6.09, giving the highest values in the morning hours. The implementation of a heat pump system aims to reduce emissions from traditional water-heating equipment and in addition to the selected refrigerant to avoid damage to the ozone layer and reduce the emission of gases which provoke the greenhouse effect. A meteorological station and temperature measuring equipment such as pyrometer and a Fluke Ti200 thermographic chamber, were used to obtain data such as radiation, ambient temperature and wind velocity.